Near-room-temperature Ag2Se / MSe nano composite thermoelectric material and preparation method thereof

Ag2Se matrix particles were synthesized by aqueous solution method and modified with MSe molecular ligands to prepare near-room temperature Ag2Se/MSe nanocomposite thermoelectric materials, which solved the problem of insufficient performance and processability of existing thermoelectric materials, and achieved efficient and controllable material preparation and excellent thermoelectric properties.

CN119768017AActive Publication Date: 2025-04-04HEFEI UNIV OF TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411780522.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-04-04
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

Existing thermoelectric materials have shortcomings in performance and processability. In particular, Bi2Te3-based materials have limited their wide application due to the scarcity of tellurium and the complex processing technology. As a potential N-type thermoelectric material, Ag2Se has a high difficulty in controlling performance stability and composition, which limits its practical application.

Method used

Ag2Se matrix particles were synthesized by aqueous solution method, and modified by MSe molecular ligands to prepare near-room temperature Ag2Se/MSe nanocomposite thermoelectric material. This method quickly completes material preparation under low temperature conditions, has the characteristics of high efficiency, controllability and accuracy, and can effectively build Ag2Se-based nanocomposite thermoelectric materials.

Benefits of technology

It has achieved large-scale rapid synthesis of high-power factor Ag2Se-based nanocomposite thermoelectric materials in the near room temperature range, significantly improving the thermoelectric properties of the material, showing a constant high average thermoelectric superiority (zTavg~1) and excellent thermal stability, and has good practical application value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119768017A_ABST
    Figure CN119768017A_ABST
Patent Text Reader

Abstract

The invention discloses a near-room-temperature Ag2Se / MSe nano composite thermoelectric material and a preparation method thereof. The preparation method comprises the following steps: synthesizing matrix Ag2Se particles through an aqueous solution method; mO metal oxide powder and Se powder are mixed and then added into an amine-thiol mixed solution, an MSe molecular ligand is obtained, then the surface of the MSe molecular ligand is modified with matrix Ag2Se particles, aftertreatment is carried out, the near-room-temperature Ag2Se / MSe nanocomposite is obtained, M is Cd or Zn, and the molar fraction of MSe in the Ag2Se / MSe nanocomposite is 2%-10%. And placing the Ag2Se / MSe nano composite material in a tubular furnace, carrying out annealing treatment in a nitrogen atmosphere, and carrying out plasma discharge sintering densification to obtain the Ag2Se / MSe nano composite thermoelectric material block. According to the preparation method, the Ag2Se material is subjected to surface functionalization treatment, so that the overhigh carrier concentration of the Ag2Se material is effectively reduced, meanwhile, phonon scattering is enhanced by using an MSe nano precipitated phase, and the Ag2Se-based thermoelectric material with high thermoelectric performance at room temperature is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of energy materials, and in particular to a near-room temperature Ag2Se / MSe nanocomposite thermoelectric material and a preparation method thereof. Background Art

[0002] Thermoelectric materials can convert heat into electricity and vice versa, playing a vital role in promoting compact cooling systems in 5G networks, seamless integration of the Internet of Things, and self-powered technologies based on body temperature. However, the potential of thermoelectric materials has not been fully explored due to the insufficient performance of existing materials, complex manufacturing processes, and many challenges in integrating materials into functional devices. Ideal thermoelectric materials need to have both high Seebeck coefficient (S) and high electrical conductivity (σ), as well as low thermal conductivity (κ). tot ) to achieve excellent thermoelectric performance. However, due to the close relationship between carrier and phonon transport, improving the thermoelectric performance coefficient (zT = σS2T / κ tot ) face great challenges. To address these issues, researchers have proposed a series of strategies, including adjusting the carrier concentration by doping or alloying, optimizing the electronic structure by bandgap engineering, and improving material properties by crystal structure modification. In addition, materials with naturally low lattice thermal conductivity are explored, and multi-scale layered structures are designed to scatter phonons across the full spectrum, thereby further reducing the thermal conductivity κ tot Therefore, the key to achieving high-performance thermoelectric materials lies in the fine engineering design of their composition and microstructure, which can not only optimize the thermoelectric performance but also improve the processability of the materials and the feasibility of practical applications.

[0003] At present, N-type thermoelectric materials near room temperature still mainly rely on Bi2Te3-based compounds as performance benchmarks. However, the scarcity of tellurium, the complex processing technology of Bi2Te3 and its poor mechanical properties significantly limit the widespread application and promotion of this type of material. In contrast, Ag2Se is considered to be a potential N-type thermoelectric material with room temperature performance comparable to that of Bi2Te3, or even the possibility of surpassing it. At about 406K, Ag2Se undergoes a phase transition from the orthorhombic β-Ag2Se phase to the cubic α-Ag2Se phase. This first-order phase transition is accompanied by significant changes in the crystal structure and electronic structure, which directly affects its transport properties. Therefore, the excellent thermoelectric performance of Ag2Se is mainly reflected in the near-room temperature range before the phase transition. However, the performance stability of Ag2Se is significantly affected by the stoichiometric ratio and defect control. This is mainly due to the weak ionicity of the Ag-Se bond, and the Ag ions are easy to migrate to the interstitial position to provide additional free electrons; at the same time, the volatility of Se at high temperature makes the carrier concentration (>10 19 cm -3) is significantly higher than the range required to achieve optimal thermoelectric performance (~10 18 cm -3 ). Excessive carrier concentration not only affects the power factor (PF = σS2) of the material, but also increases the total thermal conductivity κ tot , further limiting its thermoelectric performance. In addition, the Ag2Se materials synthesized by the traditional solid-phase melting method have great difficulty in controlling the composition, and cannot effectively regulate the grain size and grain boundary phase of the bulk, resulting in significant differences in the transport parameters of samples with the same nominal composition, which causes a large range of fluctuations in the thermoelectric figure of merit (zT). On the other hand, although the solution method provides a certain degree of advantage, its mainstream methods (such as solvothermal and hydrothermal methods) usually require time-consuming and energy-consuming high-temperature reaction equipment, and the single output is limited, which seriously limits its economic and scalable potential for practical application. Therefore, developing a preparation method with high composition control accuracy, higher cost-effectiveness and easy scalability is the key to achieving widespread application of Ag2Se materials. Summary of the invention

[0004] The purpose of the present invention is to provide a near-room temperature Ag2Se / MSe nanocomposite thermoelectric material and a preparation method thereof. The preparation method is simple, the synthesis conditions are mild and the energy consumption is low. The large-scale rapid synthesis of high power factor Ag2Se-based nanocomposite thermoelectric materials can be achieved near room temperature, and the material has good practical application value.

[0005] In one aspect of the present invention, the present invention provides a method for preparing a near-room temperature Ag2Se / MSe nanocomposite material. According to an embodiment of the present invention, the method comprises the following steps:

[0006] (1) Synthesizing the matrix Ag2Se particles by aqueous solution method;

[0007] (2) MO metal oxide powder is mixed with Se powder and added to an amine-thiol mixed solution to obtain MSe molecular ligands, and then the MSe molecular ligands are surface-modified on the matrix Ag2Se particles, and post-treated to obtain a near-room temperature Ag2Se / MSe nanocomposite material, wherein the M is Cd or Zn, and the molar fraction of MSe in the Ag2Se / MSe nanocomposite material is 2% to 10%.

[0008] In addition, the method for preparing a near-room-temperature Ag2Se / MSe nanocomposite material according to the above embodiment of the present invention may also have the following additional technical features:

[0009] In some embodiments of the present invention, in step (1), the aqueous solution method is as follows: under argon protection, AgNO3 is added to deionized water to prepare an Ag source precursor; Se powder is slowly added to an aqueous solution of NaBH4 until the reaction is completely clarified to obtain a Se source precursor; the Se source precursor is added to a preheated boiling aqueous solution of the Ag source precursor to react, and after the reaction is completed, the reaction is cooled to room temperature, washed, centrifuged, and vacuum dried to obtain Ag2Se particles.

[0010] In some embodiments of the present invention, the concentration of AgNO3 dissolved in deionized water is 0.3-0.5 mol·L -1 , the molar ratio of Se powder to NaBH4 is 1.0-1.1:2, and the molar ratio of Ag source precursor to Se source precursor is 2:0.9-1.2; the temperature of adding Se source precursor to the preheated boiling aqueous solution of Ag source precursor for reaction is 100-101.3°C, and the reaction time is 0.5-60min; the washing adopts deionized water and ethanol to wash and purify alternately 2-5 times; the centrifugal speed is 5000-8000rpm, and the centrifugal time is 1-5min; the drying adopts vacuum drying, the vacuum drying time is 6-8h, and the temperature is 60-80°C.

[0011] In some embodiments of the present invention, in step (2), the preparation method of MSe molecular ligand is as follows: under a nitrogen atmosphere, MO metal oxide powder and Se powder are dissolved in ethylenediamine and 1,2-ethanedithiol solution, and stirred at room temperature until completely dissolved to obtain MSe molecular ligand.

[0012] In some embodiments of the present invention, in step (2), the step of modifying the surface of the matrix Ag2Se particles with the MSe molecular ligand is specifically as follows: adding N-methylformamide (MFA) solution to the Ag2Se solution, adding the MSe molecular ligand after uniform dispersion, stirring for a certain period of time, centrifuging and purifying it with acetone several times, and vacuum drying to obtain the Ag2Se@MSe nanocomposite thermoelectric material.

[0013] In some embodiments of the present invention, the molar ratio of Ag2Se to MSe is 1:x%, wherein 0<x≤10; the stirring time is not less than 24 hours; the centrifugal speed is 5000-10000rpm, and the centrifugal time is 5-10min; the drying is vacuum drying, the vacuum drying time is 6-8h, and the temperature is 60-80°C.

[0014] In another aspect of the present invention, the present invention provides a near-room temperature Ag2Se / MSe nanocomposite material prepared according to the preparation method.

[0015] In another aspect of the present invention, a method for preparing a Ag2Se / MSe nanocomposite thermoelectric material is proposed. According to an embodiment of the present invention, the method comprises the following steps: placing the Ag2Se / MSe nanocomposite material in a tubular furnace, annealing the Ag2Se / MSe nanocomposite material in a nitrogen atmosphere, and densifying the Ag2Se / MSe nanocomposite thermoelectric material block by plasma discharge sintering.

[0016] In addition, the method for preparing a Ag2Se / MSe nanocomposite thermoelectric material according to the above embodiment of the present invention may also have the following additional technical features:

[0017] In some embodiments of the present invention, the annealing temperature is 350-450°C, and the heating rate is 5-15°C·min -1 , annealing time is not less than 60min; the pressure of the plasma discharge sintering is 45-60MPa, the temperature is 350-450℃, and the time is not less than 5min.

[0018] In another aspect of the present invention, the present invention provides an Ag2Se / MSe nanocomposite thermoelectric material prepared according to the Ag2Se / MSe nanocomposite thermoelectric material preparation method.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] 1) Efficient, controllable and precise preparation: The present invention proposes a new method for rapidly preparing Ag2Se / MSe nanocomposites by a controllable, large-scale and low-cost solution method at near room temperature. Compared with the traditional solid-phase melting method, the present invention adopts a "bottom-up" aqueous solution synthesis strategy, which can quickly complete the material preparation under low temperature conditions. The present invention uses MSe molecular ligands to modify the aqueous solution method to synthesize the Ag2Se matrix, which is different from any traditional hydrothermal method, solvothermal method, hot injection colloid method, etc., and can effectively construct near-room temperature Ag2Se-based nanocomposite thermoelectric materials. Compared with traditional solid-phase synthesis methods and other liquid-phase synthesis methods (such as hydrothermal method and solvothermal method), the present invention has significant advantages: the whole process does not require long-term, high-energy consumption treatment under high temperature (>1000K) conditions in solid-phase synthesis, and is not limited by high-pressure reactor equipment and capacity, and is suitable for economical and efficient large-scale preparation of Ag2Se-based bulk materials. The process is simple, easy to operate, does not require the use of expensive or complex equipment, and the preparation process has high repeatability, and has good industrial application potential.

[0021] 2) Composition regulation and microstructure optimization: In the synthesis method of Ag2Se materials, Ag precipitates are often observed, which is almost unavoidable because the composition range of pure phase Ag2Se in the phase diagram is extremely narrow. However, the present invention adopts molecular ligands prepared by the "amine-thiol" system to effectively eliminate the unavoidable Ag second phase in the Ag2Se matrix. This improvement significantly reduces the excessive carrier concentration caused by the Ag second phase, accurately controls the stoichiometric ratio of Ag2Se, and thus achieves excellent electrical transmission performance with ultra-high power factor. During the sintering process, the MSe molecular ligands further crystallize to form nanocrystals, and the grain size and grain boundary structure of the material are accurately regulated by the "pinning effect".

[0022] 3) Significantly improve near-room-temperature thermoelectric performance: During the sintering process, the MSe molecular ligands further crystallize to form nanocrystals, and the grain size and grain boundary structure of the material are precisely controlled through the "pinning effect". At the same time, this method introduces more defect structures, greatly enhancing the phonon scattering ability, thereby providing a novel and efficient solution for the coordinated optimization of the electrical and thermal properties of Ag2Se-based thermoelectric materials. The Ag2Se / MSe nanocomposite bulk prepared finally exhibits an almost constant high average thermoelectric figure of merit (zT avg ~1), and exhibits excellent thermal stability. These properties make it have great potential in practical applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a schematic diagram of the process of preparing the Ag2Se / MSe nanocomposite thermoelectric material in Comparative Example 1 and Examples 1-8 of the present invention;

[0024] Figure 2 a) TEM image of Ag2Se nanoparticles without surface modification in Comparative Example 1 of the present invention, b) TEM image of Ag2Se@CdSe powder modified with 7% CdSe molecular ligands in Example 4 of the present invention, c) TEM image of Ag2Se@ZnSe modified with 4% ZnSe molecular ligands in Example 7 of the present invention;

[0025] Figure 3a) is the X-ray diffraction pattern (XRD) of the Ag2Se / x%CdSe (x=2, 4, 6, 7, 10) nanocomposite materials in Comparative Example 1 and Examples 1-5 of the present invention, b) is an enlarged view of the (112) peak and the (121) peak in the figure a), c) is the corresponding lattice parameters of the Ag2Se / x%CdSe nanocomposite materials in the three directions a, b, and c calculated from the XRD pattern, d) is the X-ray diffraction pattern (XRD) of the Ag2Se / x%ZnSe (x=3, 4, 5) nanocomposite materials in Comparative Example 1 and Examples 6-8, and e) is an enlarged view of the (112) peak and the (121) peak in the figure d);

[0026] Figure 4 Figure 2 shows the temperature evolution of in-situ XRD patterns of a) Ag2Se and b) Ag2Se / 7%CdSe bulk in the temperature range of 323-503K and the two-dimensional plot of their intensity versus 2θ and temperature (T); c) Left: lattice parameters with temperature obtained by Rietveld refinement of XRD data; Right: reversible phase transition of Ag2Se, manifested as different crystal structure transformations between β-Ag2Se phase and α-Ag2Se phase;

[0027] Figure 5 Scanning tunneling microscope (SEM) images of Ag2Se / x%CdSe (x=0, 2, 4, 6, 7, 10) and Ag2Se / x%ZnSe (x=3, 4, 5) prepared in Examples 1-8 of the present invention;

[0028] Figure 6 In the figure, a) is the transmission electron microscope (TEM) image of the Ag2Se matrix, bc) is the STEM-EDX element mapping of the square marked area in a); d) is the TEM image of Ag2Se / 7%CdSe nanoparticles; e) dislocation defect structure of Ag2Se / 7%CdSe nanoparticles; f) lattice strain defect structure of Ag2Se / 7%CdSe nanoparticles; g) dark field STEM images of Ag2Se / 7%CdSe at different magnifications, inset: STEM-EDX element mapping; h) high-resolution TEM image of Ag2Se / 7%CdSe nanoparticles; i) TEM image of Ag2Se / 4%ZnSe; j) TEM image of part of Ag2Se / 4%ZnSe; k) the boxed area is the STEM-EDX element mapping of Ag2Se / 4%ZnSe;

[0029] Figure 7 The thermoelectric performance diagram of the nanocomposite materials of Comparative Example 1 (Ag2Se matrix), Example 4 (Ag2Se / 7%CdSe) and Example 7 (Ag2Se / 4%ZnSe) of the present invention, a) electrical conductivity σ, b) thermal conductivity κ totFigure 1. c) Thermoelectric figure of merit zT value, d) Average thermoelectric figure of merit zT in the entire temperature test range of 300-390K ave value. DETAILED DESCRIPTION

[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] Example 1

[0032] A method for preparing a near-room temperature Ag2Se / 2%CdSe nanocomposite thermoelectric material comprises the following steps:

[0033] Step 1: Prepare Ag2Se matrix particles by aqueous solution method, and react AgNO3 and Se powder according to the molar ratio of Ag:Se in Ag2Se=2:1.1. It includes the following steps:

[0034] a. First, prepare the cationic Ag source precursor AgNO3 solution, mix 60mmol of AgNO3 (10.1922g) powder and 150mL of deionized water, and stir under nitrogen protection until completely dissolved. Then heat the solution to boiling (about 101.3°C) under reflux conditions to obtain the cationic Ag source precursor.

[0035] b. Prepare the NaHSe solution, the precursor of the anionic Se source. Dissolve 60 mmol of NaBH4 (2.2698 g) in 150 mL of deionized water until it is completely dissolved. Then slowly add 33 mmol of Se (2.6057 g) powder to the solution. This step will produce a large amount of hydrogen (avoid stirring). When the bubbles gradually disappear, stir under nitrogen protection until the solution becomes almost colorless and transparent. This indicates that the Se powder has been completely reduced and the Se source precursor is obtained.

[0036] c. Rapidly inject the prepared Se source precursor into the heated and boiling cationic Ag source precursor solution. At this time, the temperature drops to 78°C. After the reaction solution boils again, keep it warm for 30 minutes. After the reaction is completed, stop stirring, cool it to room temperature in a water bath, pour out the supernatant, and wash the remaining black precipitate solution with deionized water and ethanol centrifugation three times alternately. The centrifugal speed and time of deionized water washing are 5000rpm and 1min respectively; the centrifugal speed and time of ethanol washing are 6000rpm and 1min respectively. Vacuum dry at 60°C for 6 hours to obtain Ag2Se matrix particles.

[0037] Step 2, preparation of CdSe molecular ligand, comprising the following steps:

[0038] d. 4 mmol of CdO and 4 mmol of Se powder were weighed in a molar ratio of Cd:Se = 1:1 and placed in a glass bottle filled with nitrogen. 8 mL of ethylenediamine and 0.8 mL of 1,2-ethanedithiol were injected into the above powders and stirred at room temperature for 5 minutes until completely dissolved to obtain a CdSe molecular ligand with a concentration of 87 mg / mL.

[0039] Step 3: Preparation of Ag2Se / 2%CdSe nanocomposite thermoelectric material

[0040] e. Weigh 0.3 mL of the CdSe molecular ligand solution obtained in step d in an inert gas glove box, and add a certain volume of N-methylformamide (MFA) solution under a nitrogen atmosphere to keep its concentration at 50 μL / mL. Subsequently, these solutions were mixed with 2.0 g of accurately weighed Ag2Se particles under the protection of a nitrogen atmosphere, and stirred at room temperature for 24 hours to uniformly modify the CdSe molecular ligands on the surface of the Ag2Se particles. After completion, acetone was used for purification and washing. Finally, the Ag2Se / 2%CdSe nanocomposite thermoelectric material powder was obtained by drying in a vacuum drying oven at 60°C for 8 hours.

[0041] f. The nanocomposite powder dried in step e was introduced into a tube furnace with high-purity N2 gas at 10 ° C. min. -1 The material was heated to 400°C at a heating rate of 1000 °C and annealed at 400°C for 60 minutes. After annealing, it was quickly transferred to a glove box. Then, plasma spark sintering was performed at 400°C for densification, with a pressure of 45 MPa and a holding time of 5 minutes to obtain a Ag2Se / 2%CdSe nanocomposite thermoelectric material block (size: 8.6 mm in diameter and 1.5 mm in thickness).

[0042] Example 2

[0043] A method for preparing a near-room temperature Ag2Se / 4%CdSe nanocomposite thermoelectric material, the difference between this embodiment and embodiment 1 is that in step e, 0.6 mL of the CdSe molecular complex solution obtained in step d is weighed in an inert gas glove box and then N-methylformamide (MFA) solution is added, and finally in step f, a Ag2Se / 4%CdSe nanocomposite thermoelectric material block is obtained. The remaining steps are the same as in embodiment 1.

[0044] Example 3

[0045] A method for preparing a near-room temperature Ag2Se / 6%CdSe nanocomposite thermoelectric material, the difference between this embodiment and embodiment 1 is that in step e, 0.9 mL of the CdSe molecular complex solution obtained in step d is weighed in an inert gas glove box and then N-methylformamide (MFA) solution is added, and finally in step f, a Ag2Se / 6%CdSe nanocomposite thermoelectric material block is obtained. The remaining steps are the same as in embodiment 1.

[0046] Example 4

[0047] A method for preparing a near-room temperature Ag2Se / 7%CdSe nanocomposite thermoelectric material, the difference between this embodiment and embodiment 1 is that in step e, 1.05 mL of the CdSe molecular complex solution obtained in step d is weighed in an inert gas glove box and then N-methylformamide (MFA) solution is added, and finally in step f, a Ag2Se / 7%CdSe nanocomposite thermoelectric material block is obtained. The remaining steps are the same as in embodiment 1.

[0048] Example 5

[0049] A method for preparing a near-room temperature Ag2Se / 10%CdSe nanocomposite thermoelectric material, the difference between this embodiment and embodiment 1 is that in step e, 1.5 mL of the CdSe molecular complex solution obtained in step d is weighed in an inert gas glove box and then N-methylformamide (MFA) solution is added, and finally in step f, a Ag2Se / 10%CdSe nanocomposite thermoelectric material block is obtained. The remaining steps are the same as in embodiment 1.

[0050] Example 6

[0051] A method for preparing a near-room temperature Ag2Se / 3% ZnSe nanocomposite thermoelectric material comprises the following steps:

[0052] Step 1 is the same as step 1 of Example 1.

[0053] Step 2, the preparation of ZnSe molecular ligand, comprises the following steps:

[0054] i. 4 mmol of ZnO and 4 mmol of Se powder were fully mixed in a nitrogen atmosphere at a molar ratio of Zn:Se=1:1. Then 12 mL of ethylenediamine and 1.2 mL of 1,2-ethanedithiol were injected into the above powders and stirred at room temperature for 5 min until completely dissolved, obtaining a ZnSe molecular ligand with a concentration of 43.7 mg / mL.

[0055] Step 3: Preparation of Ag2Se / 3% ZnSe nanocomposite thermoelectric material

[0056] ii. Weigh 0.67 mL of the ZnSe molecular complex solution obtained in step i in an inert gas glove box, and add a certain volume of N-methylformamide (MFA) solution in a nitrogen atmosphere to keep its concentration at 50 μL / mL. Subsequently, these solutions were mixed with 2.0 g of accurately weighed Ag2Se particles under the protection of a nitrogen atmosphere, and stirred at room temperature for 24 hours to uniformly modify the ZnSe molecular ligands on the surface of the Ag2Se particles. After completion, acetone was used for purification and washing. Finally, the Ag2Se / 3% ZnSe nanocomposite thermoelectric material powder was obtained by drying in a vacuum drying oven at 60°C for 8 hours.

[0057] iii. The nanocomposite powder dried in step ii was introduced into a tube furnace with high-purity N2 gas at 10 ° C min -1 The material was heated to 400°C at a heating rate of 1000 °C and annealed at 400°C for 60 minutes. After annealing, it was quickly transferred to a glove box. Then, plasma spark sintering was performed at 400°C for densification, with a pressure of 45 MPa and a holding time of 5 minutes to obtain a Ag2Se / 3% ZnSe nanocomposite thermoelectric material block (size: 8.6 mm in diameter and 1.5 mm in thickness).

[0058] Example 7

[0059] A method for preparing a near-room temperature Ag2Se / 4% ZnSe nanocomposite thermoelectric material, the difference between this embodiment and embodiment 6 is that in step ii, 0.9 mL of the ZnSe molecular ligand solution obtained in step i is weighed in an inert gas glove box and then N-methylformamide (MFA) solution is added, and finally step iii is performed to obtain a Ag2Se / 4% ZnSe nanocomposite thermoelectric material block. The remaining steps are the same as those in embodiment 1.

[0060] Example 8

[0061] A method for preparing a near-room temperature Ag2Se / 5% ZnSe nanocomposite thermoelectric material, the difference between this embodiment and embodiment 6 is that in step ii, 1.12 mL of the ZnSe molecular complex solution obtained in step i is weighed in an inert gas glove box and then N-methylformamide (MFA) solution is added, and finally step iii is performed to obtain a Ag2Se / 5% ZnSe nanocomposite thermoelectric material block. The remaining steps are the same as those in embodiment 1.

[0062] Comparative Example 1

[0063] The preparation method of the matrix Ag2Se thermoelectric block material is consistent with the preparation steps of the matrix Ag2Se in Examples 1-8, and mainly includes the following steps:

[0064] Take 2.0 g of the Ag2Se matrix particles prepared in step 1 of Example 1, introduce high-purity N2 gas into a tube furnace at 10 °C min -1 The Ag2Se powder was then ground with an agate mortar and poured into a graphite mold with a diameter of 8.6 mm and lined with 0.20 mm carbon paper. The mold was plasma-discharged for 5 min at a pressure of 45 MPa and a temperature of 400 °C, and finally a block with a diameter of 8.6 mm and a thickness of 1.5 mm was obtained.

[0065] The particle micrographs and element distribution diagrams of the Ag2Se / MSe (M=Cd, Zn) nanocomposite powders prepared in Examples 1-8 and Comparative Example 1 were characterized using a German Zeiss field emission scanning electron microscope AurigaZeiss (SEM). The physical phases of the Ag2Se / MSe (M=Cd, Zn) composite materials in Examples 1-8 and the block in Comparative Example 1 were characterized using a German Bruker AXSD8 ADVANCE X-ray diffractometer (XRD). The electrical conductivity (σ) and Seebeck coefficient (S) of the samples were tested using a German Lindsay Seebeck coefficient / resistance analysis system LSR-3. The thermal diffusion rate (λ) of the samples was determined using a German Lindsay laser flash analyzer LFA 1000, and the final total thermal conductivity κ of the samples was calculated. tot .

[0066] Table 1 Parameters of the Ag2Se bulk matrix prepared in Comparative Example 1 and the Ag2Se / MSe (M=Cd, Zn) nanocomposite bulk prepared in Examples 1-8

[0067] sample <![CDATA[Ag2Se / x%MSe(M=Cd,Zn)]]> Required MSe molecular ligand (mL) <![CDATA[Density (g·cm -3 )]]> Relative theoretical density Comparative Example 1 x=0 0 8.15 99.1% Example 1 x=2%,M=Cd 0.3,M=Cd 8.01 97.4% Example 2 x=4%,M=Cd 0.6,M=Cd 7.99 97.2% Example 3 x=6%,M=Cd 0.9,M=Cd 7.87 96.5% Example 4 x=7%,M=Cd 1.05,M=Cd 7.83 96.1% Example 5 x=10%,M=Cd 1.5,M=Cd 7.85 95.5% Example 6 x=3%,M=Zn 0.67,M=Zn 7.99 97.2% Example 7 x=4%,M=Zn 0.90,M=Zn 7.92 96.3% Example 8 x=5%,M=Zn 1.12,M=Zn 7.89 96.0%

[0068] The block density obtained in Comparative Example 1 and Examples 1-8 is within the theoretical density (8.22 g·cm -3 ) is between 95% and 99%.

[0069] The performance and structural morphology of the sintered samples and their cross sections were characterized by the formula zT=TσS 2 κ tot -1 (Where T is the absolute thermodynamic temperature; S is the Seebeck coefficient; σ is the electrical conductivity; κ tot is the thermal conductivity; where κ tot =λC p ρ, λ are thermal diffusion coefficients, C p is the specific heat, ρ is the bulk density) and the thermoelectric figure of merit zT is calculated.

[0070] like Figure 1As shown, after Ag2Se nanoparticles are synthesized in large quantities at near room temperature, they are added to a mixed solution of MSe (M = Cd, Zn) molecular ligands and N-methylformamide (MFA), and surface-modified Ag2Se / MSe powders are obtained after a series of precipitation, purification, and vacuum drying. Subsequently, annealing treatment and densification sintering are performed to finally obtain a tightly bound Ag2Se / MSe nanocomposite block, in which there are a large number of grain boundaries, dislocations, and MSe nanoprecipitates.

[0071] like Figure 2 As shown in the figure, a) the size distribution of Ag2Se matrix particles is relatively wide, ranging from a few hundred nanometers to about 2μm; bc) Ag2Se@MSe powder formed by surface treatment of Ag2Se matrix particles modified with MSe molecular ligands shows that this surface modification causes the edges of Ag2Se particles to soften slightly and appear more rounded. This phenomenon can be explained by the solubility of the "thiol-amine" solvent system, which can dissolve bulk inorganic materials, especially high-energy atoms on the surface of the Ag2Se matrix.

[0072] like Figure 3 As shown in Figure a), it can be seen that all characteristic peaks of the composite material block are characteristic spectral lines of the matrix Ag2Se (standard card PDF 01-071-2410), indicating that the final prepared composite material is an Ag2Se-based compound, and its components correspond to the five different bulk samples of Ag2Se / 2%CdSe, Ag2Se / 4%CdSe, Ag2Se / 6%CdSe, Ag2Se / 7%CdSe, and Ag2Se / 10%CdSe in Examples 1-5, respectively, and are all consistent with the peaks of the pure phase of Ag2Se, and no impurity peaks appear. b) The enlarged (112) peak and (121) peak in the figure also verify this situation. c) Figure shows the lattice parameters of all Ag2Se / x%CdSe samples in the a, b and c directions. The lattice parameters of all samples in each direction are consistent, which shows that the addition of CdSe molecular complexes will not change the lattice parameters. 2+ It is not doped into the lattice of the orthorhombic phase β-Ag2Se. d) The figure corresponds to three different bulk samples of Ag2Se / 3%ZnSe, Ag2Se / 4%ZnSe, and Ag2Se / 5%ZnSe in Examples 6-8, and they are all consistent with the characteristic peaks of pure phase Ag2Se, and no impurity peaks appear. e) The enlarged (112) peak and (121) peak in the figure also prove this situation.

[0073] like Figure 4 As shown, the Ag2Se thermoelectric block in Comparative Example 1 ( Figure 4 a) and the Ag2Se / 7%CdSe sample in Example 4 ( Figure 4b) In-situ XRD patterns that vary with temperature. The results show that the surface-modified nanocomposites do not affect the phase transition temperature of Ag2Se. At 403K, both samples undergo a phase transition from low-temperature orthorhombic β-Ag2Se to high-temperature cubic α-Ag2Se. c) According to the Rietveld refined XRD patterns, the ligand modification of CdSe molecules does not change the lattice parameters of Ag2Se over the entire temperature range. This indicates that CdSe exists as a second phase in the Ag2Se matrix, thus forming a nanocomposite.

[0074] like Figure 5 As shown in the figure, the cross section of the Ag2Se nanomaterial after annealing and sintering is relatively flat and the grain size is large. The grains of the Ag2Se / MSe bulk prepared by surface treatment with MSe molecular ligands gradually become finer with the increase of CdSe and ZnSe content, indicating that the cross section of the Ag2Se / MSe nanocomposite material gradually becomes denser, with more stacking wrinkles and the unevenness of the sample surface increases.

[0075] like Figure 6 As shown, ac) TEM images and STEM-EDX elemental mapping of the Ag2Se matrix show that its internal structure contains the enrichment of the Ag nanosecond phase. dh) In the TEM image of the Ag2Se / 7%CdSe nanoparticles, a large amount of stress and dislocation enrichment can be observed, and the Ag second phase disappears. The STEM-EDX elemental mapping and high-resolution electron microscopy (HRTEM) show the existence of the CdSe nanosecond phase; ik) Similarly, in the TEM image and STEM-EDX elemental mapping of the Ag2Se / 4%ZnSe nanoparticles, a large amount of nanoprecipitate phase enrichment can be observed, and no Ag second phase is observed. HRTEM confirms the existence of the ZnSe nanosecond phase.

[0076] like Figure 7 As shown in Figure 1, a) compared with the Ag2Se matrix, the conductivity σ of the sample is significantly reduced after the introduction of MSe. This is because the introduction of MSe produces a large number of dislocations, which causes these Ag interstitial atoms to be partially captured, hindering their ionization into Ag. + The Ag2Se matrix has a high carrier concentration (>10 19 cm -3 ) is gradually reduced to adjust to the most suitable level (~10 18 cm -3 b) the presence of MSe nanoprecipitates and the formation of high-density grain boundaries and dislocation defect structures in the Ag2Se / MSe samples, resulting in the thermal conductivity of all samples in Comparative Examples 1-8 κ totc) The final Ag2Se / 4%ZnSe sample has a higher peak zT at 369K max Reached 1.13, Ag2Se / 7%CdSe sample has the highest zT at 380K max The value reaches 1.05; d) it remains almost constant in the entire temperature range, and the average zT of Ag2Se / 4%ZnSe and Ag2Se / 7%CdSe samples in the temperature range of 300-390K is avg The value is greater than 1, reaching zT avg =1.08 and zT avg =1.05, is the Ag2Se matrix sample zT avg = more than twice of 0.45, showing performance comparable to that of traditional room-temperature commercial Bi2Te3-based room-temperature thermoelectric materials.

[0077] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the present invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing a near-room temperature Ag2Se / MSe nanocomposite material, characterized in that: The following steps are involved: (1) Synthesizing the matrix Ag2Se particles by aqueous solution method; (2) MO metal oxide powder is mixed with Se powder and added to an amine-thiol mixed solution to obtain MSe molecular ligands, and then the MSe molecular ligands are surface-modified on the matrix Ag2Se particles, and post-treated to obtain a near-room temperature Ag2Se / MSe nanocomposite material, wherein the M is Cd or Zn, and the molar fraction of MSe in the Ag2Se / MSe nanocomposite material is 2% to 10%.

2. The method for preparing a near-room-temperature Ag2Se / MSe nanocomposite material according to claim 1, characterized in that: In step (1), the aqueous solution method is as follows: under argon protection, AgNO3 is added to deionized water to prepare an Ag source precursor; Se powder is slowly added to an aqueous solution of NaBH4 until the reaction is completely clarified to obtain a Se source precursor; the Se source precursor is added to a preheated boiling aqueous solution of the Ag source precursor to react, and after the reaction is completed, the reaction is cooled to room temperature, washed, centrifuged, and vacuum dried to obtain Ag2Se particles.

3. The method for preparing a near-room-temperature Ag2Se / MSe nanocomposite material according to claim 2, characterized in that: The concentration of AgNO3 dissolved in deionized water is 0.3-0.5 mol·L -1 , the molar ratio of Se powder to NaBH4 is 1.0-1.1:2, and the molar ratio of Ag source precursor to Se source precursor is 2:0.9-1.2; The Se source precursor is added into the preheated boiling aqueous solution of the Ag source precursor for reaction at a temperature of 100-101.3°C and a reaction time of 0.5-60 min; The washing is performed by alternately washing with deionized water and ethanol for 2-5 times; The centrifugal speed is 5000-8000rpm, and the centrifugal time is 1-5min; The drying is performed by vacuum drying, the vacuum drying time is 6-8h, and the temperature is 60-80°C.

4. The method for preparing a near-room-temperature Ag2Se / MSe nanocomposite material according to claim 1, characterized in that: In step (2), the preparation method of the MSe molecular ligand is as follows: under a nitrogen atmosphere, MO powder and Se powder are dissolved in ethylenediamine and 1,2-ethanedithiol solution, and stirred at room temperature until completely dissolved to obtain the MSe molecular ligand.

5. The method for preparing a near-room-temperature Ag2Se / MSe nanocomposite material according to claim 1, characterized in that: In step (2), the steps of modifying the surface of the matrix Ag2Se particles with the MSe molecular ligand are specifically as follows: adding N-methylformamide solution to the Ag2Se solution, adding the MSe molecular ligand after uniform dispersion, stirring for a certain period of time, centrifuging and purifying it with acetone several times, and vacuum drying to obtain the Ag2Se@MSe nanocomposite thermoelectric material.

6. The method for preparing a near-room-temperature Ag2Se / MSe nanocomposite material according to claim 5, characterized in that: The molar ratio of Ag2Se to MSe is 1:x%, wherein 0<x≤10; The stirring time is not less than 24 hours; The centrifugal speed is 5000-10000rpm, and the centrifugal time is 5-10min; The drying is performed by vacuum drying, the vacuum drying time is 6-8h, and the temperature is 60-80°C.

7. A near-room temperature Ag2Se / MSe nanocomposite material prepared according to the preparation method according to any one of claims 1 to 6.

8. A method for preparing Ag2Se / MSe nanocomposite thermoelectric material, characterized in that: The method comprises the following steps: placing the Ag2Se / MSe nanocomposite material according to claim 7 in a tubular furnace, annealing the Ag2Se / MSe nanocomposite material in a nitrogen atmosphere, and densifying the Ag2Se / MSe nanocomposite thermoelectric material block by plasma discharge sintering.

9. The method for preparing a Ag2Se / MSe nanocomposite thermoelectric material according to claim 8, characterized in that: The annealing temperature is 350-450°C, and the heating rate is 5-15°C·min -1 , annealing time is not less than 60min; The plasma discharge sintering is performed under a pressure of 45-60 MPa, a temperature of 350-450° C., and a time of not less than 5 minutes.

10. An Ag2Se / MSe nanocomposite thermoelectric material prepared according to the preparation method according to claim 9.

Citation Information

Patent Citations

  • Preparation method of polycrystalline SnSe-based composite material with controllable growth of crystal grains

    CN117241647A

  • SnSe / PbX nano composite material and preparation method thereof

    CN118201458A

  • Preparation method of Ag2Se / AgXSe2 (X / Sb or Bi) thermoelectric composite material

    CN118234357A

  • Meat tenderizer and meat processing method using the meat thenderizer

    KR102611896B1

  • Self-tuning of carrier concentration for high thermoelectric performance

    US20120090656A1